Linguopragmatic features of the illocutionary phenomenon in speech act theory - Maxmudova , Komila Sobirjаnovna (The Lingua Spectrum, 2026)
This article presents an in-depth and systematic analysis of the linguopragmatic features of the illocutionary phenomenon within the framework of speech act theory. Illocutionary acts are examined not only as means of conveying propositional content, but also as essential mechanisms for expressing speakers’ communicative intentions, influencing interlocutors, and achieving specific pragmatic goals. The study explores the concept of illocutionary force and highlights its dependence on contextual factors, communicative situations, social roles of participants, and culturally conditioned norms of interaction. Particular attention is given to the relationship between illocution, implicature, presupposition, and the pragmatic effects that emerge in discourse. The article further analyzes the core structural components of speech acts – locution, illocution, and perlocution – emphasizing their functional roles in real communicative practices. Through theoretical discussion and illustrative examples, the author demonstrates how illocutionary expressions operate across different types of discourse and how their effectiveness can be enhanced through appropriate communicative strategies. The findings of the research contribute to the development of linguopragmatics and speech act theory by offering well-grounded insights into the nature, function, and significance of illocutionary acts. Overall, the study deepens the understanding of how illocution shapes meaning, interaction, and successful communication in linguistic and pragmatic contexts.